The Role of Preoperative Bilateral Breast Magnetic Resonance Imaging in Patient Selection for Partial Breast Irradiation in Ductal Carcinoma In Situ - Kowalchik, Kristin V. (Hindawi Publishing Corporation, 2012)

(untitled)
Purpose. Women with ductal carcinoma in situ (DCIS) are often candidates for breast-conserving therapy, and one option for radiation treatment is partial breast irradiation (PBI). This study evaluates the use of preoperative breast magnetic resonance imaging (MRI) for PBI selection in DCIS patients. Methods. Between 2002 and 2009, 136 women with newly diagnosed DCIS underwent a preoperative bilateral breast MRI at Mayo Clinic in Florida. One hundred seventeen women were deemed eligible for PBI by the NSABP B-39 (National Surgical Adjuvant Breast and Bowel Project, Protocol B-39) inclusion criteria using physical examination, mammogram, and/or ultrasound. MRIs were reviewed for their impact on patient eligibility, and findings were pathologically confirmed. Results. Of the 117 patients, 23 (20%) were found ineligible because of pathologically proven MRI findings. MRI detected additional ipsilateral breast cancer in 21 (18%) patients. Of these women, 15 (13%) had more extensive disease than originally noted before MRI, and 6 (5%) had multicentric disease in the ipsilateral breast. In addition, contralateral breast cancer was detected in 4 (4%). Conclusions. Preoperative breast MRI altered the PBI recommendations for 20% of women. Bilateral breast MRI should be an integral part of the preoperative evaluation of all patients with DCIS being considered for PBI.